Inferred Subcellular Localization of Peroxisomal Matrix Proteins of Guillardia theta Suggests an Important Role of Peroxisomes in Cryptophytes - Vasilev, Jana; Mix, Ann-Kathrin; Heimerl, Thomas; Maier, Uwe G.; Moog, Daniel (Frontiers in Plant Science, 2022)
Peroxisomes participate in several important metabolic processes in eukaryotic cells, such as the detoxification of reactive oxygen species (ROS) or the degradation of fatty acids by β-oxidation. Recently, the presence of peroxisomes in the cryptophyte Guillardia theta and other “chromalveolates” was revealed by identifying proteins for peroxisomal biogenesis. Here, we investigated the subcellular localization of candidate proteins of G. theta in the diatom Phaeodactylum tricornutum, either possessing a putative peroxisomal targeting signal type 1 (PTS1) sequence or factors lacking a peroxisomal targeting signal but known to be involved in β-oxidation. Our results indicate important contributions of the peroxisomes of G. theta to the carbohydrate, ether phospholipid, nucleotide, vitamin K, ROS, amino acid, and amine metabolisms. Moreover, our results suggest that in contrast to many other organisms, the peroxisomes of G. theta are not involved in the β-oxidation of fatty acids, which exclusively seems to occur in the cryptophyte's mitochondria.